Folk Literature in Serbian Language Teaching Before and After Curriculum Reform (Preučevanje otroške in mladinske književnosti, 2025)
Having in mind the educational possibilities of folk literature, we were interested in whether changes in the curriculum of the initial Serbian language teaching resulted in changes in the representation of this type of literature as a teaching content. In a broader sense, authors looked at the possibilities of curriculum reform to create a stimulating environment focused on pupils, based on already established traditional cultural values, but also open to contemporary social trends in which new generations will grow up. The focus of the research tasks was a comparison of the representation of folk literature as a compulsory and optional teaching content, before and after curriculum reform – in the content of curriculums and forty reading books. Content analysis shows a partially changed attitude of the reformed curriculum creators and textbook authors towards folk literature in the function of the goal and outcome of Serbian language teaching.